Synthesis and properties of donor-acceptor-substituted metal-capped fourfold-bridged cyclobutadienophanes - Gleiter, Rolf; Roers, Rolf; Claßen, Jörg; Jacobi, Albrecht; Huttner, Gottfried; Oeser, Thomas (Organometallics, 2000)
The synthesis of the superphanes 4−8 could be achieved from {(1,2,11,12-η4)-tricyclo[10.8.0.02,11]eicosa-1,11-diene-6,17-diyne}(η5-cyclopentadienyl)cobalt (15) and its methoxycarbonyl congener 14 by heating with R−CpCo(CO)2 (R = H, CH3, (CH3)5). X-ray investigations on the superphanes 3, 6, and 8 reveal distances between the two cyclobutadiene units between 2.922 Å (3) and 2.941 Å (6). Investigations by means of cyclic voltammetry show a decrease of the first oxidation potentials with increasing number of CH3 substituents at the cyclopentadienyl ligands. The comparison between the first oxidation potentials of 2−6, 4−7, and 5−8 gives evidence for a partial charge delocalization over both CpCoCb fragments of the superphanes.
Publication on Web 12/18/1999
Gesehen am 10.11.2020